ANALISIS PERTUMBUHAN EKONOMI REGIONAL DAN KETIMPANGAN PEMBANGUNAN ANTAR WILAYAH DI SUMATERA UTARA - Ditiya Puspita; Imsar Imsar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine regional economic growth and development disparities between districts/cities in North Sumatra Province. The research method uses a descriptive qualitative approach with secondary data sourced from publications of the Central Statistics Agency (BPS) and regional development planning documents. The analysis is conducted using content analysis techniques to explore growth patterns, causes of inequality, and their impact on development policies. The results show that economic growth is still concentrated in urban areas, particularly Medan City, Deli Serdang Regency, and Binjai City, while inland and island regions such as Nias and Mandailing Natal lag significantly behind. This disparity is caused by the uneven distribution of infrastructure, the concentration of investment in growth centers, and non-inclusive development policies. This study recommends the need for development policies based on local potential and equitable distribution of infrastructure to encourage more equitable economic growth across the region.